Glasgow Coma Scale in Predicting the Outcome of Patients with Altered Consciousness in Emergency Department of Cipto Mangunkusumo Hospital - tantri, aida; Wahyu, Ismail Hari; Firdaus, Riyadh (Perdatin Pusat, 2014)
Penurunan kesadaran harus ditangani dengan tepat untuk mengurangi kerusakan lebih lanjut. Glasgow coma scale (GCS) digunakan untuk menilai tingkat kesadaran pada pasien dan memprediksi outcome pasien. Penelitian ini bertujuan untuk mengetahui ketepatan Glasgow coma scale memprediksi outcome pada pasien dengan penurunan kesadaran di Instalasi Gawat Darurat RSUPN Cipto Mangunkusumo. Penelitian ini merupakan studi observasional, kohort prospektif pada 116 pasien usia ≥8 tahun dengan GCS dibawah 15 saat tiba di IGD RSCM Jakarta. Skor GCS dinilai sebanyak 1 kali ketika pasien pertama diterima. Peneliti mengevaluasi outcome dua minggu setelah perawatan dengan menggunakan kriteria GCS. Bad outcome (meninggal dan disabilitas berat) dijumpai pada 66 pasien (56,9%) dan good outcome (disabilitas sedang dan sembuh) pada 50 pasien (43,1%). Skor GCS kelompok bad outcome berbeda bermakna dengan kelompok good outcome berdasarkan analisis statistik (p<0,001). Skor GCS-E, GCS-M dan GCS-V masing-masing pasien kelompok bad outcome berbeda bermakna dengan kelompok good outcome berdasarkan analisis statistik (p<0,001). Dari hasil analisis regresi logistik, komponen GCS yang memiliki nilai prediksi terhadap outcome adalah komponen verbal dan membuka mata. Skor glasgow coma scale mampu memprediksi outcome dengan tepat pada pasien dengan penurunan kesadaran di Instalasi Gawat Darurat RSUPN Cipto Mangunkusumo. Kata kunci: Glasgow coma scale, glasgow outcome scale, penurunan kesadaran Altered consciousness must be managed immediately to reduce further damage. Glasgow Coma Scale (GCS) is used to assess the level of consciousness in citically ill patients. GCS serves as the predictor of patient outcomes. The objective of this study was to determine the accuracy of GCS in predicting outcome of patients with altered level of consciousness in Emergency Department of Cipto Mangunkusumo Hospital. This observational prospective cohort study enlisted 116 patients aged ≥18 years with GCS below 15 in the Emergency Department of Cipto Mangunkusumo Hospital. GCS was assessed at admission then it was reviewed 2 weeks after in order to assess outcome. GCS scores were classified into bad outcome (death and severe disability) and good outcome (moderate disability and good recovery). Bad outcome were found in 66 patients (56.9%) and good outcome in 50 patients (43.1%). GCS score were different significantly between both groups (p<0.001). Each of patient’s GCS-E, GCS and GCS-M-V in bad outcome groups differed significantly with good outcome group (p <0.001). Based on logistic regression analysis, verbal and eye components served a predictive value for the outcome. Glasgow Coma Scale can predict outcome in patients with altered level of consciousness. Key words: Altered consciousness, glasgow coma scale, glasgow outcome scale Reference Bhardwaj A, Kornblunth J. Evaluation of coma: a critical appraisal of popular scoring systems. Neurocrit Care. 2010;3:1−10. Jennett B. Development of Glasgow coma and outcome scale. Nepal J Neurosci. 2005;2:24−8. Maheswaran M, Adnan W, Ahmad R, Rahman A, Naing N, Abdullah J. The use of an in house scoring system scale versus Glasgow coma scale in non-traumatic altered states of consciousness patients: can it be used for triaging patients in Southeast Asian developing countries? Southeast Asian J Trop Med Public Health. 2007;38(6):1126−40. Bates D. The prognosis of medical coma. J Neurosurg Psychiatry. 2001;71:i20−3. Ting HW, Chen MS, Hseih TC, Chan CL. Good mortality prediction by Glasgow coma scale for neurosurgical patients. J Chin Med Assoc. 2010;73(3):139−43. Miah T, Hoque A, Khan R. The Glasgow coma scale following acute stroke and inhospital outcome: an observational study. J Medicine. 2009;10(1):11−4. Levati A, Farina ML, Vecchi G, Rossanda M, Morrubini M. Prognosis of severe head injuries. J Neurosurg. 1982;57:779−83. Jagger J, Jane JA, Rimel R. The Glasgowcoma scale: to sum or not to sum? Lancet. 1983;2:97. McNett M. A review of the predictive ability of Glasgow coma scale scores in head-injured patients. J Neurosci Nurs. 2007;39:68−75. Wijdicks EF, Bamlet WR, Maramattom BV, Manno EM, McClelland RL. Validation of a new coma scale: the FOUR Score. Ann Neurol. 2005;58:585−93. Budiman. Kegawatdaruratan Medik di Bidang Ilmu Penyakit Dalam: penatalaksanaan umum koma. Dalam: Aru Sudoyo, Bambang Setiyohadi, Idrus Alwi Marcellus Simadibrata, Siti Setiati, editor. Buku Ajar Ilmu Penyakit Dalam. Edisi ke-4. Jakarta: Pusat Penerbitan Departemen Ilmu Penyakit Dalam Fakultas Kedokteran Universitas Indonesia; 2006. Hlm.161−3. Settervall CH, Sousa RM, Silva SC. Inhospital mortality and the Glasgow coma scale in the first 72 hours after traumatic brain injury. Rev Latino-Am Enfermagem. 2011;19(6):1337−43.